1978
DOI: 10.1073/pnas.75.11.5506
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen synthesis in serum-free hepatocyte cultures: Stimulation by glucocorticoids

Abstract: Fibrinogen synthesis was investi ated in cultures of chicken embryo hepatocytes initiated and maintained in chemically defined serum-free medium. lI-Hydroxy glucocorticoids caused a 3-0old stimulation of fibrinogen synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
35
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 24 publications
2
35
0
Order By: Relevance
“…This behavior of albumin synthesis in our cultures is unchanged by inclusion of serum in the medium (15) and appears to be related to a decline of albumin messenger RNA (unpublished data). Although a number ofhormones have been shown to stimulate synthesis of specific plasma proteins in this culture system (8,9), none can replace the requirement of the cells for insulin to restore albumin synthesis. Insulin is also required in primary frog hepatocyte cultures for continued albumin synthesis (25).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This behavior of albumin synthesis in our cultures is unchanged by inclusion of serum in the medium (15) and appears to be related to a decline of albumin messenger RNA (unpublished data). Although a number ofhormones have been shown to stimulate synthesis of specific plasma proteins in this culture system (8,9), none can replace the requirement of the cells for insulin to restore albumin synthesis. Insulin is also required in primary frog hepatocyte cultures for continued albumin synthesis (25).…”
Section: Methodsmentioning
confidence: 99%
“…Culture medium was replaced with an equal volume of fresh medium every 24 hr unless otherwise indicated. Heparin sodium salt was included, at a concentration of 15 ,ug/ml, in medium intended for fibrinogen assay (8). Insulin (bovine pancreas, crystalline, Sigma; 24.3 units/mg) was routinely used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the mechanisms by which acute-phase reactants are induced are poorly understood. Macrophage factors, in particular interleukin I (2), and glucocorticoids (3,4) have both been implicated in induction of some acute-phase reactant proteins. We (5), Baumann et al (6), and Feinberg et al (7) have recently shown that AGP and its mRNA are induced several hundred-fold by glucocorticoids in the rat hepatoma cell line HTC.…”
mentioning
confidence: 99%